Evaluación y detección de dificultades en el proceso de enseñanza-aprendizaje que pueden ser superadas con la aplicación de las tecnologías de la información y comunicación -tic por los docentes de la unidad educativa Monseñor Santiago Fernández García de la ciudad de Cariamanga año 2015. Propuesta alternativa - Acaro Rodríguez, Rosa Alexandra (2016)
This research entitled "EVALUACIÓN Y DETECCIÓN DE DIFICULTADES EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE QUE PUEDEN SER SUPERADAS CON LA APLICACIÓN DE LAS TIC POR LOS DOCENTES DE LA UNIDAD EDUCATIVA MONSEÑOR SANTIAGO FERNÁNDEZ GARCÍA DE LA CIUDAD DE CARIAMANGA AÑO 2015. PROPUESTA ALTERNATIVA." Its purpose is to determine the problems that arise in the process of teaching and learning and the proper use of TICs can be solved. The main drawback was evident that the vast majority of teachers do not use TIC in the classroom, work continues in the traditional way withflipchart instead of a slide, copies of books rather than sharing by e or a blog for students to analyze and to make a judgment. Added to this, there is no sufficient tools to integrate TICs into the teaching-learning process, and that are not cater for the number of students, because of all the parallels in the educational unit, only 10 have a projector. 3 laboratories have distributed only one in the School San Jose, one for whole body and one for the upper level, which together account for 2,400 students in the Educational Unit. Besides the Internet bandwidth does not supply as the number of users. The overall objective of this research was "Identify the technological difficulties can be overcome by teachers of UEMSFG with the application of InformationTechnology and Communication-TIC in order to optimize the teaching-learning process." The methods used for the preparation of this research work were: inductive, deductive, analytical, statistical and scientific. The techniques used were: direct observation, surveys, one directed to teachers and other students of the Education Unit to identify the degree of use and knowledge of TIC, and interviews with leading authorities. After the investigation concludes that there is a great need to develop and updatethe tools technologists Education Unit. Also using the survey results it can be determined that teachers have the basic knowledge regarding TIC but not being implemented in the classroom. As for the results of the students mostly we have to have knowledgeand technological tools used, which is a great advantage when integrating TIC in education. Finally an alternative to consideration by the authorities and teachers to implement proposal, which aims to improve the difficulties in the process of teaching and learning that can be overcome with the implementation of TIC arises.